#TITLE_ALTERNATIVE# - VERONICA WIDYA (NIM : 12211004), RIZKY
With the high reserves of heavy oil, which reached 20% of total oil reserves in the world, heavy oil production increase done. However, the high viscosity oil that produce oil mobility and primary recovery low become a major problem in producing heavy oil. This condition can be overcome by the application of Enhanced Oil Recovery (EOR), thermal method is one of them. The most method widely used to produce heavy oil is steam flooding. By heating oil is most often done with injecting steam continuously into the reservoir so as to lower the oil viscosity. However, low viscosity and density of the steam results lower displacement efficiency due to viscous fingering, gas override and gravity segregation. In addition, sometimes the application of steam flooding is not optimal because of the heterogeneity of the reservoir that can lead channeling thus reducing the displacement efficiency and efficiency of the area and also the vertical, it also results in excessive use of steam. Some theories and experiments which successfully demonstrated the steam foam can act as a mobility control agent of steam so as to improve the total displacement efficiency. Steam foam by using surfactant may also lower the interfacial tension of oil and water so as to improve the microscopic efficiency. Simulation study comparison between the continuous steam injection method and steam foam injection method conducted to compare the oil recovery factor value of both methods and also feasibility in the application of steam foam method in the field, as well as to determine the parameters the influence the design of steam foam. Local equilibrium (LE) foam model is used as incorporated in CMG-STARSTM simulator. Simulation result gives higher total displacement efficiency that showed by recovery factor and lower remaining oil saturation for steam foam method than the cont inuous steam injection method. This can be observed by the reduction of mobility ratio and IFT and followed by decreased oil saturation that can be displaced use steam foam injection method.